2013
DOI: 10.1016/j.drugalcdep.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of nicotinic receptor antagonism II: Cardiovascular effects in rats

Abstract: Background Tobacco cessation pharmacotherapies currently are limited to nicotine itself, the partial nicotine agonists varenicline and cytisine, and the antidepressant bupropion. Compared with agonists, nicotinic antagonists such as the noncompetitive, nonselective compound mecamylamine, and the competitive, α4β2-preferring antagonist dihydro-β-erythroidine (DHβE) may be a novel approach to the treatment of tobacco smoking as both are effective antagonists of nicotine’s central effects. Considering nicotinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Varenicline is a partial agonist of the α4‐β2 nicotinic acetylcholine receptor (nAchR) and a full agonist of the α3‐β4 and α7 nAchRs. These receptors have been shown to potentially modulate cardiovascular function 11, 54, 55, 56. Varenicline activates α4‐β2 and α7 nAchRs at rates similar to those of nicotine and is a greater agonist than nicotine at the α3‐β4 nAchR 57.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varenicline is a partial agonist of the α4‐β2 nicotinic acetylcholine receptor (nAchR) and a full agonist of the α3‐β4 and α7 nAchRs. These receptors have been shown to potentially modulate cardiovascular function 11, 54, 55, 56. Varenicline activates α4‐β2 and α7 nAchRs at rates similar to those of nicotine and is a greater agonist than nicotine at the α3‐β4 nAchR 57.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors have been shown to potentially modulate cardiovascular function. 11,[54][55][56] Varenicline activates a4-b2 and a7 nAchRs at rates similar to those of nicotine and is a greater agonist than nicotine at the a3-b4 nAchR. 57 However, it is unknown whether partial activation of these receptors can lead to major changes in cardiovascular health, as the role of these receptors in modulating the cardiovascular system is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data suggest a direct role of nicotine on cardiac SIRT1-FGF21-AMPK signaling in mice fed HFD. Indeed, nicotinic receptors are present in the heart (Ni et al 2010; Jutkiewicz et al 2013). The clinical implication of this study is that smoking plus HFD lead to heart failure and other forms of cardiomyopathy and that anti-apoptotic agents might help to prevent this.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that varenicline has high efficacy in its agonist activity at α7 receptor subtypes, and may mediate nicotinic agonist-induced increases in sympathetic activity. 22 , 40 Jutkiewicz et al reported that although varenicline significantly decreased HR, it could engender all cardiovascular responses. 40 Our results showed no significant change in HR for both the acute and chronic groups, whereas there was a significant decrease in MBP values in the V2 treatment group compared with the C2 group.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 40 Jutkiewicz et al reported that although varenicline significantly decreased HR, it could engender all cardiovascular responses. 40 Our results showed no significant change in HR for both the acute and chronic groups, whereas there was a significant decrease in MBP values in the V2 treatment group compared with the C2 group. Although the change in BP was statistically significant, we believe that this result should be disregarded because of the relatively high measurements in the C2 group.…”
Section: Discussionmentioning
confidence: 99%